Preparation method of super-hydrophobic coating for waterproofing of fibers or fabrics

By performing hydroxylation treatment on fibers or fabrics and condensation reactions of tetraethyl silicate, combined with the synergistic action of alkoxysilane and cationic surfactant, silicon-oxygen composite nanoparticles are generated, which solves the problem of unreasonable nanocomponent usage and inappropriate substrate treatment in the preparation process of fluorine-free superhydrophobic materials, and significantly improves hydrophobic properties.

CN119736787APending Publication Date: 2025-04-01SHENZHEN YISHANG NANO TECH CO LTD

Patent Information

Application Number
CN202510065076.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

During the preparation process of existing fluorine-free superhydrophobic materials, there are unreasonable nanocomponent usage and inappropriate substrate treatment, resulting in a degradation of hydrophobic performance.

Method used

Impurities are removed by stirring the fibers or fabrics in aqueous ethanol solution and sonicating them in anhydrous ethanol. Then a condensation reaction is carried out in tetraethyl silicate to form a hybrid layer, followed by addition of alkoxysilane and cationic surfactant, and the silicon oxygen composite nanoparticles are generated through hydrolysis and polycondensation reaction to construct a hydrophobic layer.

Benefits of technology

The hydrophobic properties of fibers or fabrics are significantly improved, so that they still maintain good superhydrophobic effects after washing and friction tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention particularly relates to a preparation method of a super-hydrophobic coating for waterproofing of fibers or fabrics. The method comprises the following steps: S1, hydroxylating fibers or fabrics; s2, dipping the hydroxylated fiber or fabric in tetraethyl silicate, reacting at room temperature, washing with deionized water, and drying; s3, dissolving a hexadecyl trimethyl ammonium halide cationic surfactant in deionized water, heating and stirring to obtain a mixed solution A, and adding alkoxy silane into the deionized water, and performing ultrasonic treatment at room temperature to obtain a mixed solution B; s4, mixing the mixed solution A and the mixed solution B to obtain a mixed solution C, adding a dispersing agent into the mixed solution C, and stirring to obtain a super-hydrophobic agent; and S5, coating the pretreated fiber or fabric with a super-hydrophobic agent in a dipping or spraying manner. According to the method, a preliminary rough structure is formed on the surface of the fiber or the fabric, and then the surface roughness is further increased by coating the silica composite nanoparticles, so that the hydrophobic property of the coating is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of super hydrophobic coating preparation, and specifically to a method for preparing a super hydrophobic coating for waterproofing fibers or fabrics. Background Art

[0002] With the continuous improvement of living standards, people's functional requirements for daily necessities are also increasing, and functional fabrics have gradually become the focus of people's attention. At present, relevant researchers have developed a series of functional fabrics, such as antibacterial cotton fabrics, conductive fabrics, UV-proof fabrics, super-hydrophobic fabrics, etc. Among them, super-hydrophobic fabrics are highly favored due to their excellent self-cleaning ability and daily anti-fouling effect. They are widely used in various life scenes, not only in medical and military fields, but also in daily life.

[0003] At present, common super-hydrophobic fabrics are mainly made by fluorinated super-hydrophobic finishing agents. Such finishing agents usually contain fluorinated compounds with low surface energy, such as perfluoro long-chain silanes or fluorinated polyethers. These compounds give fabrics super-hydrophobic properties by forming low surface energy and micro-nano rough structures on the fabric surface. However, fluorinated super-hydrophobic fabrics have some significant disadvantages: ① Environmental issues: Fluorinated compounds are difficult to degrade naturally, have bioaccumulation and environmental persistence, and pose a potential threat to ecosystems and human health. Therefore, many fluorinated compounds such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonyl compounds (PFOS) have been banned worldwide. ② Insufficient durability: Fluorinated super-hydrophobic coatings have poor mechanical strength and durability, and are prone to lose super-hydrophobic properties during friction, washing or wear. This limits its durability and reliability in practical applications. ③ Complex preparation process: The preparation process of fluorinated super-hydrophobic fabrics is usually complicated, involving multiple chemical reactions and coating processes. In addition, the price of fluorinated materials is high, which increases the production cost.

[0004] Therefore, many scholars have tried to explore a fluorine-free super-hydrophobic material for fabrics. A Chinese patent with a publication number of CN115748237B discloses a fluorine-free super-hydrophobic material and a preparation method thereof. The substrate is first pretreated in an alkaline aqueous solution of a silane coupling agent, and then an organosilicon polymer solution is placed on the surface of the pretreated substrate. The fluorine-free super-hydrophobic material is obtained by thermal curing. The organosilicon polymer solution includes modified nanoparticles, organosilicon polymers and organic solvents. However, the amount of nanoparticles added is relatively large (3 to 10). Due to the large amount of nanoparticles added, agglomeration may occur, thereby affecting the dispersion effect, and ultimately resulting in an uneven coating, which is easy to fall off and causes a decrease in hydrophobic performance over a long period of use. A Chinese patent with announcement number CN119083160A discloses a method for preparing a fluorine-free super-hydrophobic nano-silica cotton fabric, in which nano-silica is modified in turn by three silane coupling agents, trichlorooctadecylsilane, KH-560 and hexadecyltrimethoxysilane, to prepare a super-hydrophobic modified nano-silica coating. However, the main component of the hydrophobic material in this application is still nano-silica, and it is conceivable that the amount added will be relatively large, resulting in a poor dispersion effect. Secondly, the selected substrate is not pretreated, which may affect the adhesion performance of the super-hydrophobic material on the substrate during the coating process.

[0005] In summary, the existing preparation of fluorine-free superhydrophobic materials has problems such as unreasonable dosage of nano components and improper substrate treatment resulting in decreased hydrophobic performance. Therefore, it is urgent to propose a method for preparing superhydrophobic materials for fibers or fabrics to solve the problems existing in the prior art. Summary of the invention

[0006] In view of the problems existing in the preparation of fluorine-free super-hydrophobic materials, such as unreasonable dosage of nano components and improper substrate treatment leading to decreased hydrophobic performance, the present application proposes a method for preparing a super-hydrophobic coating for waterproofing fibers or fabrics.

[0007] The technical solution of this application is as follows: A method for preparing a super-hydrophobic coating for waterproofing fibers or fabrics comprises the following steps: Step S1. The substrate is washed with an aqueous solution of ethanol to remove impurities on the surface of the fiber or fabric and then dried. The dried substrate is then immersed in anhydrous ethanol and subjected to ultrasonic treatment at room temperature, and then dried again to obtain a hydroxylated substrate. Step S2. The hydroxylated substrate is immersed in tetraethyl silicate and reacted at room temperature for 24 to 36 hours, and then washed and dried with deionized water to obtain a pretreated substrate for use; Step S3. adding a hexadecyltrimethylammonium halide cationic surfactant to deionized water, heating and stirring until dissolved, to obtain a mixed solution A; adding an alkoxysilane to deionized water and ultrasonically treating at room temperature to obtain a mixed solution B; Step S4. Mix the mixed solution A and the mixed solution B in a volume ratio of 1:3-5, stir and react at room temperature to obtain a mixed solution C, and then add a dispersant to the mixed solution C and stir to obtain a super hydrophobic agent; Step S5. applying the super hydrophobic agent prepared in step S4 to the pretreated substrate prepared in step S2 by dipping or spraying to obtain a super hydrophobic coating on the substrate; The substrate is fiber or fabric.

[0008] Preferably, in step S1, During the washing process, the volume fraction of the ethanol aqueous solution is 50%, the stirring washing time is 30-40 minutes, the drying temperature is 60-70°C, and the drying time is 10-12 hours; During the ultrasonic treatment process, the ultrasonic treatment time is 15-30 minutes, the ultrasonic frequency is 60-100 kHz, the drying temperature is 60-70°C, and the drying time is 10-12 hours.

[0009] Preferably, in step S2, the immersion process is accompanied by stirring, the rotation speed is 100-230 r / min, and the drying temperature is 60-70°C.

[0010] Preferably, in step S3, the mass ratio of the hexadecyltrimethylammonium halide cationic surfactant to deionized water is 1:100-150, the heating temperature is 60-70°C, the stirring speed is 400r / min, and the hexadecyltrimethylammonium halide cationic surfactant is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.

[0011] Preferably, in step S3, the volume ratio of alkoxysilane to deionized water is 1:30-50; the ultrasonic frequency is 60-100 kHz, and the ultrasonic time is 5-10 min; and the alkoxysilane is trimethoxysilane or methyltriethoxysilane.

[0012] Preferably, the stirring speed in step S4 is 300 r / min, and the stirring time is 1.5-4 h.

[0013] Preferably, in step S4, 0.5-1 g of a dispersant is added to every 300 mL of the mixed solution C, and the dispersant is sodium carboxymethyl cellulose or hydroxyethyl cellulose.

[0014] Preferably, in step S5, The impregnation method is: impregnating the pretreated substrate into the super hydrophobic agent for 30 to 50 minutes, and forming a super hydrophobic coating on the substrate after drying; The spraying method is: the super hydrophobic agent is applied at a concentration of 1.0 to 8.0 mg / cm² per square centimeter, ventilated for 1 hour at room temperature, and then dried to form a super hydrophobic coating on the substrate.

[0015] The beneficial effects of this application are as follows: The present application can effectively remove impurities such as grease, stains, dust, etc. on the surface of the fiber or fabric by stirring and washing the fiber or fabric with an ethanol-water solution. The cavitation effect produced by ultrasound in anhydrous ethanol can make the ethanol molecules come into more complete contact with the fiber or fabric surface, hydroxylating the fiber surface and generating a large number of hydroxyl (-OH) groups.

[0016] The present application uses anhydrous ethanol ultrasonic treatment to hydroxylate the surface of the fiber or fabric. These hydroxyl groups can undergo a condensation reaction with the silanol groups (-Si(OH)4) in tetraethyl silicate to form silicon-oxygen bonds (-Si-O-Si-), forming a strong hybrid layer. This hybrid layer makes the rough structure of the fiber or fabric more obvious, can increase the contact area between the fiber surface and water droplets, and form more contact points of water droplets on the surface, thereby improving the hydrophobicity of the fiber or fabric surface. Although the hydrophobic effect at this time has not yet reached the level of super-hydrophobicity, it has laid the foundation for subsequent super-hydrophobic modification.

[0017] The alkoxysilane of the present application undergoes a hydrolysis reaction in water to generate silanol (Si(OH)4) and the corresponding alcohol (such as methanol, ethanol, etc.). The generated silanol molecules form a silica network through a dehydration polycondensation reaction, and gradually aggregate to form silica nanoparticles. The size and shape of these particles can be adjusted by controlling the reaction conditions. The hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride of the present application forms a micellar structure in the solution, and these micelles can be used as templates to guide the formation of silicon-oxygen composite nanoparticles. The long-chain alkyl part of the surfactant faces the air to form a hydrophobic layer, which helps to build a hydrophobic structure on the surface of the nanoparticles. The cationic surfactant can be adsorbed on the surface of the silicon-oxygen composite nanoparticles to form a double electric layer with a positive charge, increase the electrostatic repulsion between the particles, prevent the aggregation and sedimentation of the particles, and improve the dispersion stability of the particles. The long-chain alkyl part of the cationic surfactant has a low surface energy. When it is adsorbed on the surface of the silicon-oxygen composite nanoparticles, it can reduce the overall surface energy of the coating. Low surface energy helps to reduce the interaction between water molecules and the surface, making it more difficult for water droplets to spread on the surface, and further enhancing the hydrophobicity of the coating. The synergistic effect of cationic surfactants and alkoxysilanes makes the silicon-oxygen composite nanoparticle coating not only have a rough microstructure but also have the characteristics of low surface energy.

[0018] The present invention first forms a rough structure by hydroxylation treatment on the fiber or fabric surface and condensation reaction of tetraethyl silicate. The coating of silicon-oxygen composite nanoparticles further increases the surface roughness, allowing water droplets to form more contact points on the surface, so that the hydrophobicity of the coating is significantly improved. DETAILED DESCRIPTION

[0019] In order to further explain the technical means and effects adopted by the present application to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present application are described in detail below in combination with the preferred embodiments.

[0020] With the continuous improvement of people's living standards, the functional demand for daily necessities is growing, and functional fabrics have gradually become a hot spot of concern. At present, researchers have developed a variety of functional fabrics, including antibacterial cotton fabrics, conductive fabrics, UV-proof fabrics and super-hydrophobic fabrics. Among them, super-hydrophobic fabrics are popular because of their excellent self-cleaning performance and daily antifouling effect, but because fluorine-containing hydrophobic materials are used in existing super-hydrophobic materials, they have excellent hydrophobicity and chemical corrosion resistance, and have high thermal stability and good weather resistance, so that they can maintain stable performance under various harsh environments. However, there are also some shortcomings, such as polluting the environment, poor durability, and complex preparation process. Based on many personnel, they began to study fluorine-free super-hydrophobic materials. The applicant, by reading the materials, tries to explore fluorine-free super-hydrophobic materials. First, the surface of the fiber or fabric is cleaned, and impurities such as grease, stains, dust on the fiber or fabric surface are removed, and then the fiber or fabric surface is hydroxylated, and then condensed with the silanol group in tetraethyl silicate to form a strong hybrid layer. However, preliminary tests show that the contact angle is between 110 and 115°, and the hydrophobic effect at this time has not yet reached the level of super-hydrophobicity (the contact angle is greater than 150°, indicating that the material has super-hydrophobicity), but it has laid the foundation for subsequent super-hydrophobic modification. Therefore, the applicant continues to try to add super-hydrophobic materials on the fibers or fabrics that have been preliminarily hydrophobically treated, in order to achieve a synergistic effect. After reading the materials, silica nanoparticles are generated by the hydrolysis and polycondensation reaction of alkoxysilanes, and the micellar structure of hexadecyltrimethylammonium halide cationic surfactants is used as a template to guide the formation of silicon-oxygen composite nanoparticles, and a hydrophobic layer is constructed on its surface. Cationic surfactants are adsorbed on the surface of silicon-oxygen composite nanoparticles to form a double electric layer with a positive charge, increase the electrostatic repulsion between particles, and improve dispersion stability. At the same time, its long-chain alkyl part reduces the coating surface energy, reduces the interaction between water molecules and the surface, and enhances the hydrophobicity of the coating. The synergistic effect of cationic surfactants and alkoxysilanes gives the coating a rough microstructure and low surface energy characteristics, showing excellent hydrophobic properties. The super-hydrophobic agent prepared at this time already has super-hydrophobic properties, but after standing for 24 hours, the applicant found that the super-hydrophobic agent had slight stratification, which was not conducive to subsequent use. Therefore, the applicant added a dispersant to the super-hydrophobic agent and continued to observe for 72 hours without stratification. At this point, a super-hydrophobic agent with super-hydrophobic properties was prepared.

[0021] Example 1 Step S1: A cotton fabric (containing 95% cotton and 5% polyester fiber) of size 20 cm*20 cm was stirred and washed with a 50% volume fraction ethanol aqueous solution for 35 minutes to remove impurities on the surface of the cotton fabric. The cotton fabric was then dried at 65°C for 11 hours. Next, the dried cotton fabric was immersed in anhydrous ethanol and subjected to ultrasonic treatment at room temperature at a frequency of 95 kHz for 25 minutes. After the ultrasonic treatment, the cotton fabric was dried again at 65°C for 11 hours to obtain a hydroxylated cotton fabric.

[0022] Step S2: The hydroxylated cotton fabric is immersed in tetraethyl silicate and reacted at room temperature for 30 hours. During the immersion process, stirring is maintained at a speed of 150 r / min. After the reaction is completed, the cotton fabric is washed twice with deionized water and then dried at 65° C. for 10 hours to obtain the pretreated cotton fabric for standby use.

[0023] Step S3: Hexadecyltrimethylammonium bromide and deionized water were mixed at a mass ratio of 1:120, heated to 65°C, and stirred at a speed of 400 r / min until the surfactant was completely dissolved to obtain a mixed solution A. At the same time, trimethoxysilane and deionized water were mixed at a volume ratio of 1:40, and ultrasonically treated at room temperature with an ultrasonic frequency of 80 kHz for 8 minutes to obtain a mixed solution B.

[0024] Step S4: Mix the mixed solution A and the mixed solution B in a volume ratio of 1:4, and stir at room temperature at a speed of 300 r / min for 3 hours to obtain a mixed solution C. Then, sodium carboxymethyl cellulose is added to the mixed solution C, and 0.7 g of a dispersant is added per 300 mL of the mixed solution C, and the mixture is stirred evenly to obtain a super hydrophobic agent.

[0025] Step S5: The super hydrophobic agent prepared in step S4 is coated on the cotton fabric prepared in step S2 by dipping. The dipping method is: the cotton fabric is dipped into the super hydrophobic agent for 40 minutes, then taken out and dried at 65° C. for 10 hours to obtain the super hydrophobic cotton fabric.

[0026] Example 2 Step S1: A cotton fabric (containing 95% cotton and 5% polyester fiber) of size 20 cm*20 cm was stirred and washed with a 50% volume fraction ethanol aqueous solution for 40 minutes to remove impurities on the surface of the cotton fabric. The washed cotton fabric was then dried at 60°C for 10 hours. Next, the dried fiber or fabric was soaked in anhydrous ethanol and subjected to ultrasonic treatment at room temperature with an ultrasonic frequency of 100 kHz for 15 minutes. After the ultrasonic treatment, the cotton fabric was dried again at 70°C for 12 hours to obtain a hydroxylated cotton fabric.

[0027] Step S2: The hydroxylated cotton fabric is immersed in tetraethyl silicate and reacted at room temperature for 36 hours. During the immersion process, stirring is maintained at a speed of 230 r / min. After the reaction is completed, the cotton fabric is washed twice with deionized water and then dried at 60° C. for 10 hours to obtain the pretreated cotton fabric for standby use.

[0028] Step S3: The hexadecyltrimethylammonium halide cationic surfactant hexadecyltrimethylammonium chloride was mixed with deionized water at a mass ratio of 1:100, heated to 70°C, and stirred at a speed of 400 r / min until the surfactant was completely dissolved to obtain a mixed solution A. At the same time, methyltriethoxysilane was mixed with deionized water at a volume ratio of 1:50, and ultrasonically treated at room temperature with an ultrasonic frequency of 100 kHz for 5 minutes to obtain a mixed solution B.

[0029] Step S4: Mix the mixed solution A and the mixed solution B in a volume ratio of 1:3, and stir at room temperature at a speed of 300 r / min for 3 hours to obtain a mixed solution C. Then, a dispersant hydroxyethyl cellulose is added to the mixed solution C, and 0.5 g of the dispersant is added to every 300 mL of the mixed solution C, and the mixture is stirred evenly to obtain a super hydrophobic agent.

[0030] Step S5: The super hydrophobic agent prepared in step S4 is applied to the cotton fabric prepared in step S2 by spraying. The spraying method is: the super hydrophobic agent is sprayed on the pretreated cotton fabric at an amount of 1.0 mg / cm² per square centimeter, and then ventilated at room temperature for 1 hour and dried at 65°C for 10 hours to obtain a super hydrophobic cotton fabric.

[0031] Example 3 Step S1: A polyester fiber (100% polyester fiber) of size 20 cm*20 cm was stirred and washed with a 50% volume fraction ethanol aqueous solution for 40 minutes to remove impurities on the surface of the fiber fabric. The washed fiber fabric was then dried at 70°C for 10 hours. Next, the dried fiber fabric was immersed in anhydrous ethanol and subjected to ultrasonic treatment at room temperature at a frequency of 60 kHz for 30 minutes. After the ultrasonic treatment, the fiber fabric was dried again at 70°C for 10 hours to obtain a hydroxylated fiber fabric.

[0032] Step S2: The hydroxylated fiber fabric is immersed in tetraethyl silicate and reacted at room temperature for 24 to 36 hours. During the immersion process, stirring is maintained at a speed of 100 r / min. After the reaction is completed, the cotton fabric is washed twice with deionized water and then dried at 60° C. for 10 hours to obtain a pretreated fiber fabric for standby use.

[0033] Step S3: Hexadecyltrimethylammonium bromide and deionized water were mixed at a mass ratio of 1:150, heated to 60°C, and stirred at a speed of 400 r / min until the surfactant was completely dissolved to obtain a mixed solution A. At the same time, methyltriethoxysilane and deionized water were mixed at a volume ratio of 1:30, and ultrasonically treated at room temperature with an ultrasonic frequency of 60 kHz for 10 minutes to obtain a mixed solution B.

[0034] Step S4: Mix the mixed solution A and the mixed solution B in a volume ratio of 1:5, and stir at room temperature at a speed of 300 r / min for 1.5 hours to obtain a mixed solution C. Then, sodium carboxymethyl cellulose is added to the mixed solution C, and 1 g of a dispersant is added per 300 mL of the mixed solution C, and the mixture is stirred evenly to obtain a super hydrophobic agent.

[0035] Step S5: The super hydrophobic agent prepared in step S4 is applied to the fiber fabric prepared in step S2 by spraying. The spraying method is: the super hydrophobic agent is sprayed on the pretreated cotton fabric at a dosage of 8.0 mg / cm² per square centimeter, and then ventilated at room temperature for 1 hour and dried at 65°C for 10 hours to obtain a super hydrophobic fiber.

[0036] Example 4 Step S1: A cotton fabric (containing 95% cotton and 5% polyester fiber) of size 20 cm*20 cm was stirred and washed with a 50% volume fraction ethanol aqueous solution for 30 minutes to remove impurities on the surface of the fiber or fabric. The washed fiber or fabric was then dried at 65°C for 10 hours. Next, the dried fiber or fabric was immersed in anhydrous ethanol and subjected to ultrasonic treatment at room temperature at an ultrasonic frequency of 80 kHz for 20 minutes. After the ultrasonic treatment, the fiber or fabric was dried again at 70°C for 12 hours to obtain a hydroxylated cotton fabric.

[0037] Step S2: The hydroxylated cotton fabric is immersed in tetraethyl silicate and reacted at room temperature for 24 hours. During the immersion process, stirring is maintained at a speed of 200 r / min. After the reaction is completed, the cotton fabric is washed twice with deionized water and then dried at 65° C. for 10 hours to obtain the pretreated cotton fabric for standby use.

[0038] Step S3: Hexadecyltrimethylammonium chloride and deionized water were mixed at a mass ratio of 1:110, heated to 65°C, and stirred at a speed of 400 r / min until the surfactant was completely dissolved to obtain a mixed solution A. At the same time, trimethoxysilane and deionized water were mixed at a volume ratio of 1:35, and ultrasonically treated at room temperature with an ultrasonic frequency of 90 kHz and a treatment time of 8 minutes to obtain a mixed solution B.

[0039] Step S4: Mix the mixed solution A and the mixed solution B in a volume ratio of 1:4.5, and stir at room temperature at a speed of 300 r / min for 2 hours to obtain a mixed solution C. Then, sodium carboxymethyl cellulose is added to the mixed solution C, and 0.6 g of a dispersant is added per 300 mL of the mixed solution C, and the mixture is stirred evenly to obtain a super hydrophobic agent.

[0040] Step S5: The super hydrophobic agent prepared in step S4 is coated on the cotton fabric prepared in step S2 by dipping. The dipping method is: the cotton fabric is dipped into the super hydrophobic agent for 35 minutes, then taken out and dried at 65° C. for 10 hours to obtain the cotton fabric.

[0041] Example 5 Step S1: A fiber fabric (100% polyester fiber) of size 20 cm*20 cm was stirred and washed with a 50% volume fraction ethanol aqueous solution for 35 minutes to remove impurities on the surface of the fiber fabric. The washed fiber fabric was then dried at 70°C for 10 hours. Next, the dried fiber fabric was immersed in anhydrous ethanol and subjected to ultrasonic treatment at room temperature at a frequency of 70 kHz for 25 minutes. After the ultrasonic treatment, the fiber fabric was dried again at 70°C for 12 hours to obtain a hydroxylated fiber fabric.

[0042] Step S2: The hydroxylated fiber fabric is impregnated with tetraethyl silicate and reacted at room temperature for 35 hours. During the impregnation process, stirring is maintained at a speed of 180 r / min. After the reaction is completed, the cotton fabric is washed twice with deionized water and then dried at 65° C. for 10 hours to obtain a pretreated fiber material for use.

[0043] Step S3: Hexadecyltrimethylammonium halide cationic surfactant hexadecyltrimethylammonium bromide and deionized water are mixed at a mass ratio of 1:140, heated to 70°C, and stirred at a speed of 400 r / min until the surfactant is completely dissolved to obtain a mixed solution A. At the same time, alkoxysilane trimethoxysilane and deionized water are mixed at a volume ratio of 1:45, and ultrasonically treated at room temperature with an ultrasonic frequency of 85 kHz and a treatment time of 10 minutes to obtain a mixed solution B.

[0044] Step S4: Mix the mixed solution A and the mixed solution B in a volume ratio of 1:4, and stir at room temperature at a speed of 300 r / min for 3.5 hours to obtain a mixed solution C. Then, hydroxyethyl cellulose is added to the mixed solution C, and 0.9 g of a dispersant is added per 300 mL of the mixed solution C, and the mixture is stirred evenly to obtain a super hydrophobic agent.

[0045] Step S5: The super-hydrophobic agent prepared in step S4 is applied to the fiber fabric prepared in step S2 by spraying. The spraying method is as follows: the super-hydrophobic agent is sprayed on the pretreated cotton fabric at a dosage of 4 mg / cm² per square centimeter, and then ventilated at room temperature for 1 hour and dried at 65°C for 10 hours to obtain a super-hydrophobic fiber fabric.

[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that the surface of the cotton fabric in step S1 of this comparative example is not subjected to hydroxylation treatment.

[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that the cotton fabric in step S2 of this comparative example is not immersed in tetraethyl silicate for treatment.

[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S4 of this comparative example, the mixed solution A and the mixed solution B are mixed at a volume ratio of 1:10.

[0049] Comparative Example 4 The difference between this comparative example and Example 1 is that in step S4 of this comparative example, the mixed solution A and the mixed solution B are mixed in a volume ratio of 1:1.

[0050] Performance Testing The surface wetting properties of the super-hydrophobic fabrics in Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the model of the contact angle meter was FCA2000A; the test was performed by dripping ink, pure milk, tap water and tea water on the surface of the super-hydrophobic fabric, and then a standard washing test was performed using a drum washing machine according to the household washing and drying program for textile testing in GB / T8629-2017. A hydrophobic fabric was placed in the test, each piece was 20cm*20cm in size, and each piece had a mass of 50g±5g. Each piece of washing material was overlapped and sewn along the four sides, and washed and dried with water. The total mass of the sample and the washing material was (2.0±0.1) kg. 20g of standard detergent was added to the standard washing cycle. After the washing cycle was completed, the sample was taken out of the washing machine, and the dehydrated sample was flattened and hung, with the length direction being the vertical direction to avoid distortion. The sample was hung on a rope and a rod, and the surface wetting properties of the hydrophobic fabric were measured again after drying in the static air of the natural environment. The results are shown in Table 1.

[0051] Table 1 The super-hydrophobic fabrics in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to mechanical friction tests according to the standard GB / T3920-2008 "Fabric Color Fastness Test". The size of the sample to be tested was 5 cm*1 cm. The fabric sample was fixed and clamped at both ends of the test platform. A friction block with a gravity of 9 N was placed directly above the fabric. A standard friction cloth was placed between the sample fabric and the friction block. The friction block ran at a speed of 2 frictions / s, and one friction cycle per second. After the friction cycle was completed, the sample was removed and the surface wetting properties were tested. Only tap water was used for the test. The contact angles of the samples in Comparative Examples 1 to 5 and Comparative Examples 1 to 4 were not tested for friction. See Table 1. The contact angles of the samples that were tested for friction are shown in Table 2.

[0052] Table 2 It can be found from the above results that the preparation method of the present application has a good super-hydrophobic effect, and after washing and friction tests, it still has a good super-hydrophobic effect, wherein comparative examples 1 to 4 have a super-hydrophobic effect when not washed and friction tested, but after washing and friction tests, the effect is not ideal, which may be due to the fact that the fabric has not been pre-treated, or the ratio of mixed solution A and mixed solution B is not appropriate, resulting in a larger or smaller particle size of silicon-oxygen composite nanoparticles, resulting in a weaker adsorption force of the fabric, which is easily washed off or rubbed off, and in the preparation method of the present application, the hydroxylation treatment on the fiber or fabric surface and the condensation reaction of tetraethyl silicate have formed a preliminary rough structure. The coating of silicon-oxygen composite nanoparticles further increases the roughness of the surface, so that the water droplets form more contact points on the surface, so that the hydrophobic performance of the coating is significantly improved.

[0053] The above is only a preferred embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application has been disclosed as a preferred embodiment as above, it is not intended to limit the present application. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present application. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A method for preparing a super-hydrophobic coating for waterproofing fibers or fabrics, characterized in that: The steps include: Step S1. The substrate is washed with an aqueous solution of ethanol to remove impurities on the surface of the fiber or fabric, and then dried. The dried substrate is then immersed in anhydrous ethanol and subjected to ultrasonic treatment at room temperature, and then dried again to obtain a hydroxylated substrate. Step S2. The hydroxylated substrate is immersed in tetraethyl silicate and reacted at room temperature for 24 to 36 hours, and then washed and dried with deionized water to obtain a pretreated substrate for use; Step S3. adding a hexadecyltrimethylammonium halide cationic surfactant to deionized water, heating and stirring until dissolved, to obtain a mixed solution A; adding an alkoxysilane to deionized water and ultrasonically treating at room temperature to obtain a mixed solution B; Step S4. Mix the mixed solution A and the mixed solution B in a volume ratio of 1:3-5, stir and react at room temperature to obtain a mixed solution C, and then add a dispersant to the mixed solution C and stir to obtain a super hydrophobic agent; Step S5. applying the super hydrophobic agent prepared in step S4 to the pretreated substrate prepared in step S2 by dipping or spraying to obtain a super hydrophobic coating on the substrate; The substrate is fiber or fabric.

2. A method for preparing a super-hydrophobic coating for waterproofing fibers or fabrics according to claim 1, characterized in that: In the step S1, During the washing process, the volume fraction of the ethanol aqueous solution is 50%, the stirring washing time is 30-40 minutes, the drying temperature is 60-70°C, and the drying time is 10-12 hours; During the ultrasonic treatment process, the ultrasonic treatment time is 15-30 minutes, the ultrasonic frequency is 60-100 kHz, the drying temperature is 60-70°C, and the drying time is 10-12 hours.

3. The method for preparing a super-hydrophobic coating for waterproofing fibers or fabrics according to claim 1, characterized in that: In the step S2, the immersion process is accompanied by stirring, the rotation speed is 100-230 r / min, and the drying temperature is 60-70°C.

4. The method for preparing a super-hydrophobic coating for waterproofing fibers or fabrics according to claim 1, characterized in that: In step S3, the mass ratio of the hexadecyltrimethylammonium halide cationic surfactant to deionized water is 1:100-150, the heating temperature is 60-70° C., the stirring speed is 400 r / min, and the hexadecyltrimethylammonium halide cationic surfactant is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.

5. The method for preparing a super-hydrophobic coating for waterproofing fibers or fabrics according to claim 1, characterized in that: In step S3, the volume ratio of alkoxysilane to deionized water is 1:30-50; the ultrasonic frequency is 60-100 kHz, and the ultrasonic time is 5-10 min; the alkoxysilane is trimethoxysilane or methyltriethoxysilane.

6. The method for preparing a super hydrophobic coating for waterproofing fibers or fabrics according to claim 1, characterized in that: The stirring speed in step S4 is 300 r / min, and the stirring time is 1.5-4 h.

7. The method for preparing a super hydrophobic coating for waterproofing fibers or fabrics according to claim 1, characterized in that: In the step S4, 0.5-1 g of a dispersant is added to every 300 mL of the mixed solution C, and the dispersant is sodium carboxymethyl cellulose or hydroxyethyl cellulose.

8. The method for preparing a super hydrophobic coating for waterproofing fibers or fabrics according to claim 1, characterized in that: In the step S5, The impregnation method is: impregnating the pretreated substrate into the super hydrophobic agent for 30 to 50 minutes, and forming a super hydrophobic coating on the substrate after drying; The spraying method is: the super hydrophobic agent is applied at a concentration of 1.0 to 8.0 mg / cm² per square centimeter, ventilated for 1 hour at room temperature, and then dried to form a super hydrophobic coating on the substrate.

Citation Information

Patent Citations

  • Fluorine-free super-hydrophobic material and preparation method thereof

    CN115748237B

  • Preparation method of fluoride-free super-hydrophobic nano silicon dioxide cotton fabric

    CN119083160A

Cited By

  • Wear-resistant super-hydrophobic yarn with core-shell structure as well as preparation device and preparation method of wear-resistant super-hydrophobic yarn

    CN122147686A